Poxvirus-encoded serpins do not prevent cytolytic T cell-mediated recovery from primary infections - Müllbacher, Arno; Wallich, Reinhard; Moyer, Richard W.; Simon, Markus M. (The journal of immunology, 1999)
Previous observations that the highly conserved poxvirus-encoded serpins inhibit cytotoxic activities of alloreactive CTL via granule and/or Fas-mediated pathways was taken to indicate their involvement in immune evasion by poxviruses. We now show that interference with 51Cr release from target cells by ectromelia and cowpoxvirus is limited to alloreactive but not MHC-restricted CTL. The data are in support of the paramount importance of CTL and its effector molecule perforin in the recovery from primary ectromelia virus infection and question the role of serpins in the evasion of poxviruses from killing by CTL. Further analysis of poxvirus interference with target cell lysis by alloreactive CTL revealed that suppression primarily affects the Fas-mediated, and to a lesser extent, the granule exocytosis pathway. Serpin-2 is the main contributor to suppression for both killing pathways. In addition, inhibition of lysis was shown to be both target cell type- and MHC allotype-dependent. We hypothesize that differences in TCR affinities and/or state of activation between alloreactive and MHC-restricted CTL as well as the quality (origin) of target cells are responsible for the observed phenomenon.